Functionalized Aza-BODIPYs and Their Use in the Synthesis of Aza-BODIPY-Based Complex Systems - Yadav, Bharti; Ravikanth, Mangalampalli (Synlett, 2023)
In this account, we present syntheses of various functionalized aza-boron-dipyrromethene dyes (aza-BODIPYs) in which the functional groups are directly introduced at the 2- or 6-positions of the aza-BODIPYs or on aryl rings present at the 1-, 3-, 5-, and 7-positions of the aza-BODIPYs. Some of these functionalized aza-BODIPYs have been used for the synthesis of aza-BODIPY-based energy-transfer cassettes and light-harvesting complexes.1 Introduction2 Monofunctionalized Aza-BODIPYs2.1 2-/6-Monofunctionalized Aza-BODIPYs2.2 1-/3-/5-/7-Monofunctionalized Aza-BODIPYs3 Difunctionalized Aza-BODIPYs.3.1 2,6-Difunctionalized Aza-BODIPYs3.2 3,5-Difunctionalized Aza-BODIPYs3.3 1,7-Difunctionalized Aza-BODIPYs4 Miscellaneous5 Conclusion
Keywords: azadipyrromethene–boron difluoride complexes; BODIPYs; aza-BODIPYs; dyes; energy-transfer cassettes; light harvesting